The Association Between Multitasking and Multi-Patient Care Skills in a Simulated Patient Care Video Game Among Second Year Medical Students Based on Specialty Choice. (August 2022) - Korand, Sridevi; Fung, Cha Chi; Cohen, Sammy; Talbot, Thomas B.; Fischer, Susan; Luu, Cindy; Sargsyan, Mariam; Ben-Isaac, Eyal; Espinoza, Juan; Chang, Todd P.
Background and Objective: Healthcare providers require multitasking and multi-patient care skills, and training programs do not formally incorporate curricula specifically for multitasking skills to trainees. The medical education community is in equipoise on whether multitasking ability is a fixed trait. Furthermore, it is unclear whether multitasking ability affects those who gravitate toward careers that demand it, particularly among medical students deciding on a specialty. We sought to define the association between specialty choice, multitasking abilities and multi-patient care delivery among pre-clinical medical students. For this study, we examined both efficiency and accuracy metrics within multitasking and whether they were different between students choosing specialties. Methods: This was a planned cross-sectional sub-study focused on 2nd year medical students (MS-IIs) within a parent study evaluating multi-patient care skills using a serious game (VitalSigns:ED TM ) depicting a pediatric emergency department. Subjects completed a Multitasking Ability Test (MTAT) and five VitalSigns:ED gameplays. The predictor variable was specialty choice, categorized into multitasking and non-multitasking groups. Outcome variables measuring efficiency and diagnostic accuracy were obtained from the MTAT and the game. The primary analysis was a Mann–Whitney U test, and secondary analyses employed Spearman Rank correlations. Results: Twelve students applied to multitasking specialties and 18 applied to others. Those in the multitasking specialties had faster MTAT completions than the other cohort (29.8 vs. 59.7 sec, 95%CI difference -0.9 to -39.8 sec). Differential diagnoses were higher in multitasking specialties in VitalSigns:ED (2.03 vs. 1.06, 95%CI difference +0.05 to +1.54) but efficiency metrics in the game did not differ. Conclusion: Multitasking and multi-patient care performance show some association with preferred specialty choices for MS-IIs prior to clinical exposure.